An investigation of knowledge management practice and attitudes by information technology departments within organisations - Pervan, Graham; Ellison, Ruth (Curtin University of Technology, 2002)
Much research as been conducted on knowledge management (KM) in order to improve how organisations handle this valuable resource . Little is known, however, of how the providers of the knowledge management technologies, the organisation's IT people, handle their own knowledge management technologies. this study has focused on how IT departments and people "practice what they preach" in this area. A survey was conducted among large organisations which reveals there is a recognised need for KM but it is not pert of their formal goals. There are many KM technologies in use, however, and a positive attitude exists towards their adoption in the IT departments of these organisations.